PENGARUH PENERAPAN METODE RESITASI TERHADAP HASIL BELAJAR SISWA PADA KELAS XI IPS SMA - Irawati, Intan (Jurnal Pendidikan Sosiologi dan Humaniora, 2018)
The purpose of this study to determine the effect of learning with the method of recitation of student learning outcomes sociology subjects class XI IPS SMA Negeri 5 Pontianak. Form of quasi experimental research (quasy experimental research). The sample of this research are 74 students, 37 students of experimental group (XI IPS 1) and 37 students of Control group (XI IPS 2). Technique of collecting data of direct observation, indirect communication, documenter study and data collection tool in the form of observation and multiple choice test in the form of pre-test and post test. The data obtained in the pre-test obtained average in experimental class 70,02 and class control 70.05. on the post-test experimental class has an average of 78.32 and the control class is 74.18. Hypothesis testing using t-test (F-Test Two-Sample Assuming Equal Variances Test) in the experiment class post-test shows the statistical value t obtained is 2.400691499 and p-value 0.009474866. by using decision based on p-value, at Î± = 0,05 can be concluded significant value 0,05 (0,05 0.009474866) hence there is difference of result of post-test experiment class and control class hence Ho refused and Ha accepted. Based on the data obtained, the Alternative Hypothesis (Ha) is accepted.